A Sociological Analysis of "OK Boomer". (March 2022) - Mueller, Jason C.; McCollum, John
The year 2019 was the year of "OK Boomer" (OKb). From The New York Times to the New Zealand legislature, OKb emerged as a pop cultural phenomenon. For some, this phrase represents a battle of the generations wherein Baby Boomers are fed up with the utopian demands of younger generations, while younger generations see Baby Boomers as stubbornly conservative and out of touch. Alternatively, some dismiss the generational warfare trope and demand we see society for what it "really is"—one defined by class warfare . By deploying theories of politics, ideology, and cultural change from Mark Fisher, Fredric Jameson, Slavoj Žižek, and Franco Berardi, we offer a theoretical framework through which the emergence and proliferation of OKb can be understood. We find OKb to be embedded within the logic of capitalist realism, where younger generations' cynical usage of this meme represents a muddled attempt to cognitively map within 21st century postmodernity.